Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.5380/ef.v0i21.69716
|View full text |Cite
|
Sign up to set email alerts
|

Vídeos Educativos em Aleitamento Materno: Educação em Saúde Online

Abstract: Resumo: O aleitamento materno é uma das principais práticas de promoção à saúde, a qual proporciona inúmeros benefícios para mãe e filho, atuando principalmente na redução da morbimortalidade infantil. Todo conhecimento acerca do aleitamento materno tem como ferramenta facilitadora a educação em saúde, no qual a informação chega à população por meio dos profissionais de saúde, visando reduzir o desmame precoce. O enfermeiro é um dos profissionais responsáveis pela educação em saúde, ainda, a Tecnologia de Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…Although this type of technology contributes to the role of nurses in their educational practices, in the literature, there is little production in this topic (11) . In an extensive literature review in six informational resources, conducted by the authors of the current study, no Brazilian article was found on the production and validation of an educational video developed by health professionals, including nurses, to be used by pregnant women, postpartum women and their families, aiming to encourage BF, which presents itself as a knowledge gap and justifies the accomplishment of this research.…”
Section: Introductionmentioning
confidence: 99%
“…Although this type of technology contributes to the role of nurses in their educational practices, in the literature, there is little production in this topic (11) . In an extensive literature review in six informational resources, conducted by the authors of the current study, no Brazilian article was found on the production and validation of an educational video developed by health professionals, including nurses, to be used by pregnant women, postpartum women and their families, aiming to encourage BF, which presents itself as a knowledge gap and justifies the accomplishment of this research.…”
Section: Introductionmentioning
confidence: 99%
“…O uso de vídeos educativos é indispensável por facilitar e modificar o sistema de ensino de aula expositiva padrão, e pode contribuir positivamente para a autonomia do usuário. Nesta perspectiva esta forma de ensino é fortemente recomendada para profissionais de saúde, entre eles, o enfermeiro, uma vez que ainda são poucas as produções relacionadas a tecnologias educativas no âmbito da saúde, sendo necessário que outras produções sejam realizadas (Scorupski, et. al.…”
Section: Discussionunclassified
“…However, lactation physiology includes a set of complex and abstract contents ( 9 ) , related to hormones and their role in producing breast milk ( 10 ) . Consequently, educational technologies can be effective mediating tools for teaching and learning, such as videos on BF content ( 11 ) , motivation ( 12 ) , and self-efficacy ( 13 ) in breastfeeding. Investing in technologies addressing this topic highlights the importance of using technologies to mediate BF promotion content.…”
Section: Introductionmentioning
confidence: 99%